2005
DOI: 10.1002/ceat.200500013
|View full text |Cite
|
Sign up to set email alerts
|

Phenol Removal from Aqueous Solutions by Tamarind Nutshell Activated Carbon: Batch and Column Studies

Abstract: Activated carbons prepared from tamarind nutshell, an agricultural waste by-product, have been examined for the removal of phenol from aqueous solutions. The activated carbon was prepared by sulfuric acid activation. Both batch and column studies were performed for the sorption of phenol. The kinetic data were fitted to the models of Lagergren, pseudo-second-order and intraparticle diffusion, and closely followed the pseudo-second-order chemisorption model. The Freundlich and Langmuir isotherm models were well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 19 publications
3
22
0
1
Order By: Relevance
“…It can be concluded that the rate of phenol binding with activated carbon is more at initial stages, which gradually decreases and becomes almost constant after a period of 300 min. Similar types of observations have already been reported by several authors (Banat et al, 2004;Goud et al, 2005). Numerous kinetic models have been proposed to elucidate the mechanism by which pollutants may be adsorbed.…”
Section: Kinetics Of Phenol Adsorption Processsupporting
confidence: 67%
See 2 more Smart Citations
“…It can be concluded that the rate of phenol binding with activated carbon is more at initial stages, which gradually decreases and becomes almost constant after a period of 300 min. Similar types of observations have already been reported by several authors (Banat et al, 2004;Goud et al, 2005). Numerous kinetic models have been proposed to elucidate the mechanism by which pollutants may be adsorbed.…”
Section: Kinetics Of Phenol Adsorption Processsupporting
confidence: 67%
“…The production of activated carbons from such wastes converts unwanted, surplus waste, of which billions of kilograms are produced annually, to useful valuable adsorbents. There are a quite large number of studies regarding the preparation of activated carbons from agricultural wastes (Kadirvelu et al 2003;Nag et al, 1999), nuts , nutshells (Ahmadpour and Do, 1997;Goud et al, 2005), fruit stones (Lussier et al, 1994), bagasse (Mohan et al, 2002), coirpith (Kadirvelu et al, 2001), oil palm waste (Lua and Guo, 1998) and agricultural residues from sugarcane (Blanco Castro et al, 2000), rice (Shrinivasan et al, 1998) and peanut (Periasamy and Namasivayam, 1996), sawdust (Marquez-ontesinos et al, 2001) and canes from some easy-growing wood species (Basso et al, 2002;Maci'as et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to adsorption percentage, for all the pH values essayed, low initial concentration and high temperature increased the % of phenol adsorbed on the shell, the highest value being also obtained for the lowest pH. At pH values lower that the pK a value (9.99), the degree of ionization of phenol decreases (Goud et al, 2005) and thus its capacity to be adsorbed by chestnut shell increases. The analysis of the results obtained has suggested that the optimum adsorption conditions were the natural pH of the solutions (around 5.5) for both contaminants and 25ºC for cadmium adsorption and 60ºC for phenol adsorption.…”
Section: +mentioning
confidence: 88%
“…Quanto maior a concentração, maior a carga da solução, aumentando assim a transferência de massa (transferência de soluto da fase líquida para a fase sólida) e a força motriz (diferença entre a concentração de soluto na fase sólida e a concentração de soluto na fase líquida) (Goud et al, 2005 material zeolítico e aumenta a dispersão axial (Padmesh et al, 2005;Aksu, et al, 2007 com o aumento da vazão o efluente passa a ter menos tempo de contato com o adsorvente e portanto a velocidade de transferência de massa aumenta (Saadi et al, 2013).…”
Section: Efeito Da Concentração Inicial Do áCido Laranjaunclassified